STRATEGI PENGEMBANGAN OBYEK WISATA PANTAI DI KABUPATEN LAMPUNG SELATAN - Suyadi - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2011)
Coast Tourism as a business engaged in the service of visitors is an important benchmark insustainability efforts so that consumer confidence needs to be invested on its business, to givesatisfaction to customers and ultimately consumers will give the trust and loyalty after satisfaction ofthe company (tourist attraction).To give confidence and satisfaction that can lead to consumer loyalty in tourismmanagement should be aware of consumer perceptions of tourism objects in order to know theposition of tourism objects in the eyes of consumers among the other attractions in South Lampungso it can be determined what strategies will be used.